2021
DOI: 10.1002/acm2.13217
|View full text |Cite
|
Sign up to set email alerts
|

Treatment planning of volumetric modulated arc therapy and positioning optimization for hippocampal‐avoidance prophylactic cranial irradiation

Abstract: Background: Hippocampal-avoidance prophylactic cranial irradiation (HA-PCI) offers potential neurocognitive benefits but raises technical challenges to treatment planning. This study aims to improve the conventional planning method using volumetric modulated arc therapy (VMAT) technique and investigate a better patient's head positioning to achieve a high quality of HA-PCI treatment plans.Methods: The improved planning method set a wide expansion of hippocampus as a special region for dose decline. The whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Yuen 30 and Sood et al 31 proved that VMAT could decrease the dose of HP. Fu et al 32 designed a inclined head four full-arc VMAT plan for 16 patients who had whole-brain hippocampal avoidance, and the plan could decrease the Dmax of HP. Sun et al 33 studied the whole-brain prophylactic irradiation of 15 cases of NSCLC and found that VMAT could improve HP protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuen 30 and Sood et al 31 proved that VMAT could decrease the dose of HP. Fu et al 32 designed a inclined head four full-arc VMAT plan for 16 patients who had whole-brain hippocampal avoidance, and the plan could decrease the Dmax of HP. Sun et al 33 studied the whole-brain prophylactic irradiation of 15 cases of NSCLC and found that VMAT could improve HP protection.…”
Section: Discussionmentioning
confidence: 99%
“… 31 proved that VMAT could decrease the dose of HP. Fu et al 32 . designed a inclined head four full‐arc VMAT plan for 16 patients who had whole‐brain hippocampal avoidance, and the plan could decrease the Dmax of HP.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (47) demonstrated that tilting the head at an angle of approximately 11°improved the dose distribution and reduced the irradiated dose in the hippocampus during HA-WBRT using the VMAT technique. Fu et al (48) showed that the maximum and mean doses to the hippocampus from the modified VMAT regimen were 7.88 Gy and 6.32 Gy, respectively, which were significantly lower than those from the conventional VMAT regimen, and the maximum dose was lower than that from Tomo, with a significant dose advantage for tilted head positioning (Figure 3).…”
Section: Photon Rt Techniques Volumetric Arc Intensity-modulated Rtmentioning
confidence: 98%
“…Fu et al. ( 48 ) showed that the maximum and mean doses to the hippocampus from the modified VMAT regimen were 7.88 Gy and 6.32 Gy, respectively, which were significantly lower than those from the conventional VMAT regimen, and the maximum dose was lower than that from Tomo, with a significant dose advantage for tilted head positioning ( Figure 3 ).…”
Section: Photon Rt Techniquesmentioning
confidence: 99%
“…Exploring the feasibility of treating a large number of brain metastases with conventional C-arm linac, a new technique called piecewise volumetric modulated arc therapy (P-VMAT) was applied in this study. Recently, the technique was proposed by our group for WBRT with hippocampal sparing to improve plan quality and better spare hippocampus [ 19 , 20 ]. This study designed P-VMAT plans for WBRT + SIB with a large number of brain metastases and compared it with HT.…”
Section: Introductionmentioning
confidence: 99%